Strengthening the critical thinking skill through the six-hat thinking model in pancasila education - Oktaviani, Linda; Aulia, Ullu Yandi; Murdiono, Mukhamad; Suharno, Suharno (Intelektual Pustaka Media Utama, 2024)
This study aims to provide a comprehensive analysis of the implementation of Pancasila learning with the goal of improving critical thinking skills through the application of the six thinking hats model. The research adopts a descriptive approach utilizing qualitative methods. The study was conducted at the Faculty of Engineering, Universitas Negeri Yogyakarta. The participants were selected using purposive techniques based on specific criteria and considerations to ensure the collection of targeted information. Specifically, the research focused on students enrolled in the Manufacturing Engineering Class D. Data collection for this study involved the use of observation, interviews, and documentation techniques. To ensure data validity, triangulation techniques were employed by the researchers. Data analysis followed an interactive model based on the framework developed by Miles and Huberman, encompassing data reduction, data presentation, and conclusion drawing. The six thinking hats learning model significantly improved students' critical thinking skills and character values. This approach enables students to approach problems from multiple perspectives, becoming more responsive to social issues and navigating real-world challenges. These fosters heightened awareness of societal matters, enabling students to contribute meaningfully to social progress.